Multi Source Electric Vehicles: Smooth Transition Algorithm for Transient Ripple Minimization - Oubelaid, Adel; Taib, Nabil; Rekioua, Toufik; Bajaj, Mohit; Blazek, Vojtech; Prokop, Lukas; Misak, Stanislav; Ghoneim, Sherif S M (Sensors (Basel, Switzerland), 2022)
Any engineering system involves transitions that reduce the performance of the system and lower its comfort. In the field of automotive engineering, the combination of multiple motors and multiple power sources is a trend that is being used to enhance hybrid electric vehicle (HEV) propulsion and autonomy. However, HEV riding comfort is significantly reduced because of high peaks that occur during the transition from a single power source to a multisource powering mode or from a single motor to a multiple motor traction mode. In this study, a novel model-based soft transition algorithm (STA) is used for the suppression of large transient ripples that occur during HEV drivetrain commutations and power source switches. In contrast to classical abrupt switching, the STA detects transitions, measures their rates, generates corresponding transition periods, and uses adequate transition functions to join the actual and the targeted operating points of a given HEV system variable. As a case study, the STA was applied to minimize the transition ripples that occur in a fuel cell-supercapacitor HEV. The transitions that occurred within the HEV were handled using two proposed transition functions which were: a linear-based transition function and a stair-based transition function. The simulation results show that, in addition to its ability to improve driving comfort by minimizing transient torque ripples and DC bus voltage fluctuations, the STA helps to increase the lifetime of the motor and power sources by reducing the currents drawn during the transitions. It is worth noting that the considered HEV runs on four-wheel drive when the load torque applied on it exceeds a specified torque threshold; otherwise, it operates in rear-wheel drive.
Keywords: Computer Simulation; motorová vozidla; Algorithms; Motor Vehicles; fuel cell (FC); počítačová simulace; zdroje elektrické energie; operating point; transition function; supercapacitor (SC); elektřina; řízení motorových vozidel; Electric Power Supplies; Electricity; Automobile Driving; soft transition algorithm; algoritmy; hybrid electric vehicle